Performance and Nutrient Utilization of Growing Rabbits Fed Graded Levels of Raw Bambara Groundnut [Vigna subterranean (L.) Verdc] Offal Diets - Amaefule, K.U.; Mbonu, U.E.; Amaka, V. (Pakistan Journal of Nutrition, 2011)
Performance and nutrient utilization of growing rabbits (N = 30) fed graded levels of raw Bambara groundnut [Vigna subterranean (L.) Verdc] offal (BGO) diets were determined in a Completely Randomized Design (CRD). There were five treatments each replicated three times with two rabbits per replicate. The inclusion levels of BGO in the diets were 0, 5, 10, 15 and 20%. Measurements were live weight, weight gain, feed and nutrient intakes, feed conversion ratio, feed cost and carcass quality. Also measured were nutrients voided, nutrient retention and apparent digestibility coefficient of nutrients. Results showed that 15% BGO diet improved daily weight gain (19.16 g), final live weight (1.18 kg), feed conversion ratio (2.56) and lowered cost per kg live weight gain (Naira 76.55) of rabbits than other diets. Increased level of BGO in the diets resulted in a significant (p<0.05) decrease in total feed cost. Rabbits fed 20% BGO diet had higher CP (18.92 g) and CF (11.31 g) intakes, significantly (p<0.05) higher faecal DM (98.58 g), OM (88.97 g) and faecal nitrogen (0.04 g) than rabbits fed other diets. The diet of 20% BGO also depressed coefficient of apparent digestibility of ether extract (85.28%), CF (65.80%), crude ash and NFE (89.54%) compared to other diets. It was concluded that growing rabbits could be fed diets containing up to 15% BGO to enhance daily weight gain and reduce feed cost, which would not adversely affect nutrient intake, coefficient of apparent digestibility and nutrient utilization.